2001
DOI: 10.1152/ajpheart.2001.280.6.h2689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diacetyl monoxime and cytochalasin D on ventricular fibrillation in swine right ventricles

Abstract: Whether or not the excitation-contraction (E-C) uncoupler diacetyl monoxime (DAM) and cytochalacin D (Cyto D) alter the ventricular fibrillation (VF) activation patterns is unclear. We recorded single cell action potentials and performed optical mapping in isolated perfused swine right ventricles (RV) at different concentrations of DAM and Cyto D. Increasing the concentration of DAM results in progressively shortened action potential duration (APD) measured to 90% repolarization, reduced the slope of the APD r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 35 publications
11
100
2
Order By: Relevance
“…These characteristics deviate from those observed in our previous studies in a similar rabbit 2-dimensional ventricular myocardium in the presence of BDM, where VTs were more stable and lasted longer (VTs lasting > 30 s were 17% -29%) (18,19). The slope of APD restitution of ventricular muscle, which is known to determine the stability of wavefronts during functional reentry (33), was shown to be reduced significantly by BDM in favor of its stabilization, whereas unaffected or increased by cytochalasin D (22,34). VTs induced after single treatment with ISP were more stable and lasted longer than without ISP.…”
Section: Vts Of Sw Reentrycontrasting
confidence: 90%
See 2 more Smart Citations
“…These characteristics deviate from those observed in our previous studies in a similar rabbit 2-dimensional ventricular myocardium in the presence of BDM, where VTs were more stable and lasted longer (VTs lasting > 30 s were 17% -29%) (18,19). The slope of APD restitution of ventricular muscle, which is known to determine the stability of wavefronts during functional reentry (33), was shown to be reduced significantly by BDM in favor of its stabilization, whereas unaffected or increased by cytochalasin D (22,34). VTs induced after single treatment with ISP were more stable and lasted longer than without ISP.…”
Section: Vts Of Sw Reentrycontrasting
confidence: 90%
“…In the present study, VTs were induced by modified cross-field stimulation in the presence of cytochalasin D as an excitation-contraction uncoupler, since modification of steady-state and dynamic action potential configu- ISP ration in cardiac cells by this compound is much less than that by 2,3-butanedione monoxime (BDM) (22). The VTs induced under control conditions were unstable and terminated soon (VTs lasting > 5 s were only 3%).…”
Section: Vts Of Sw Reentrymentioning
confidence: 75%
See 1 more Smart Citation
“…16 A time point at 10% depolarization in the upstroke phase and a time point at 90% repolarization in its repolarization phase were identified for each action potential signal, and their interval was measured as APD at 90% repolarization (APD90). The distribution of APD90 values in the recording area was displayed as color gradient maps with 1.33 ms steps ranging from red (the shortest) to blue (the longest).…”
Section: Signal Processingmentioning
confidence: 99%
“…Electromechanical uncouplers work by a variety of methods, but most have an effect upon the actin-myosin cytoskeleton which is responsible for contraction. Electromechanical uncouplers should be used with care, as some studies have shown that these agents can affect various parameters of the cardiac AP and may also affect the dynamics of ventricular fibrillation (VF) (Baker et al, 2004;Biermann et al, 1998;Hyashi et al, 2003;Lee et al, 2001). …”
Section: Pre/post-conditioning Of Optical Datamentioning
confidence: 99%